-2-(3x+3)=4x-5(x-3)

Simple and best practice solution for -2-(3x+3)=4x-5(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2-(3x+3)=4x-5(x-3) equation:


Simplifying
-2 + -1(3x + 3) = 4x + -5(x + -3)

Reorder the terms:
-2 + -1(3 + 3x) = 4x + -5(x + -3)
-2 + (3 * -1 + 3x * -1) = 4x + -5(x + -3)
-2 + (-3 + -3x) = 4x + -5(x + -3)

Combine like terms: -2 + -3 = -5
-5 + -3x = 4x + -5(x + -3)

Reorder the terms:
-5 + -3x = 4x + -5(-3 + x)
-5 + -3x = 4x + (-3 * -5 + x * -5)
-5 + -3x = 4x + (15 + -5x)

Reorder the terms:
-5 + -3x = 15 + 4x + -5x

Combine like terms: 4x + -5x = -1x
-5 + -3x = 15 + -1x

Solving
-5 + -3x = 15 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-5 + -3x + x = 15 + -1x + x

Combine like terms: -3x + x = -2x
-5 + -2x = 15 + -1x + x

Combine like terms: -1x + x = 0
-5 + -2x = 15 + 0
-5 + -2x = 15

Add '5' to each side of the equation.
-5 + 5 + -2x = 15 + 5

Combine like terms: -5 + 5 = 0
0 + -2x = 15 + 5
-2x = 15 + 5

Combine like terms: 15 + 5 = 20
-2x = 20

Divide each side by '-2'.
x = -10

Simplifying
x = -10

See similar equations:

| 240x-24x=4 | | 6y+10+4x=180 | | 11z-5=5z+7 | | -5(3x-25)=2(x-2)-75 | | 6/7x8/15= | | 9-2(2x+5)+4x-12= | | 7x^2+2=18 | | -39x-10x=18+31 | | 7y+4(y-6)=4(y+z)-2 | | 4x+25=100-x | | 4a-8=2a+4 | | .6y=.2x+1.2 | | 50=20 | | 0.25x+2=7 | | 5y+10=5x | | 10b^2=810 | | .6y=-.2x+2.4 | | Y7/2x-4 | | -3(2t-2)+4t=3t-7 | | 2+4x=3(-x+2)-25 | | Log(4w+8)=log(2w-9) | | -4x+9y=15 | | ln(9)=4x | | -8r^2=72 | | 15x^2-65x+60=0 | | -80/16 | | .8x+.25(80)=.4(120) | | .5(x+20)+1.3x=91 | | -203=-7(-7x-20) | | 70/25 | | 12x+4y+17x-y+90=180 | | 6-5y=2y-8 |

Equations solver categories